ANALISIS CITRA PASAR TRADISONAL TERHADAP LOYALITAS KONSUMEN PASAR TAMBUNG (STUDI PASAR TRADISIONAL DI DESA TAMBUNG KECAMATAN PADEMAWU KABUPATEN PAMEKASAN) - Rachman Hakim; A. Rofiqi Fauzi (Yos Soedarso Economic Journal (YEJ), 2020)
The market is a part of life that is needed by humans whose development is adjusted to the customs of customary norms in a certain area. so that the market becomes a means of economic activity that supports and facilitates the needs of the community. In a more modern sense a market is a mechanism that allows supply and demand both in a physical and non-physical sense. Traditional markets have always been known as a unique market among the community in meeting household needs and also have an important role in advancing economic growth in Indonesia. Because it can open business opportunities by involving the livelihoods of the community it also has an advantage in competing naturally. With goods sold, merchants can be bargained by the buyer, so that the price that occurs is the agreement of the seller and the buyer. Traditional markets are usually carried out with management without modern technological devices and they have more middle and lower class traders who are scattered, both in villages, small cities and big cities with an average operating period from dawn to noon or evening. The results of this research show the independent variables consisting of Price (X1), Quality (X2), Physical Environment (X3). to the dependent variable, namely consumer loyalty (Y), the R value of 0.656 or 65.6%, that is, the relationship between the independent variable and the dependent variable is unidirectional and strong. Meanwhile, R squared or the determinant of R is 0.430 or 4.30% simultaneously, while the rest (100% -56.6% = 34.4%) is influenced by other factors examined in this study.Keywords : Price; Quality; Physical Environment.